The inequality we want: How much is too much? - Alice Krozer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
A key aspect defining the contemporary income distribution is the (increasing) share the top holds compared to the rest. This paper shows that income concentration increases towards the very top of the distribution, while the shares the middle- and upper-middle-income groups hold, remain stable across countries and over time. Traditional indicators less sensitive to changes at the extremes of the distribution might obscure inequality's actual dimension, and thus help perpetuate it. To avoid this, the ratio of the income share of the top 5 per cent over that of the bottom 40 per cent, denominated Palma v.2, could function as a complementary indicator for the measurement of inequality.
Keywords: D31; D63; I3; 330; inequality; income distribution; overty; Palma; Gini coefficient